Renal ultrasound findings and vesicoureteral reflux in children hospitalised with urinary tract infection. Issue 6 (1st June 2002) - Mahant, S; Friedman, J; MacArthur, C
Abstract : Aims: To determine the sensitivity, specificity, and predictive values of renal ultrasound findings for vesicoureteral reflux (VUR). Methods: Retrospective review of the ultrasound and voiding cystourethrogram (VCUG) results of 162 children under 5 years of age admitted with their first episode of urinary tract infection (UTI) over a two year period. Ultrasound findings were considered suggestive of VUR if "dilatation of the pelvi-calyces", "dilatation of the ureters", or "dilatation of the collecting system" of one or both kidneys was reported. Results: A total of 162 patients were eligible for inclusion (median age 85 days; 71 (44%) were female). The prevalence of VUR was 22%. Ultrasound findings were positive for VUR in 14 of 35 patients with confirmed VUR on VCUG, and positive in 30 of 127 patients without VUR on VCUG. Of 21 patients who had a normal ultrasound but showed VUR on VCUG, 14 had grade II reflux, five grade III reflux, and two grade IV reflux. The sensitivity and specificity of ultrasound in suggesting VUR were 40% and 76%, respectively. The positive predictive value of ultrasound in suggesting VUR was 32%; the negative predictive value was 82%. Conclusion: Renal ultrasound findings are neither sensitive nor specific for VUR in children with a first UTI.